Destabilization of Pedicle Screws and Migration of Connecting Rod into the Posterior Cranial Fossa in a Patient After Posterior Spondylosynthesis with a Screw System - I. V. Burova; E. A. Litvinenko; S. A. Kurilchik; M. M. Erovenko; A. N. Velichkin (Неотложная медицинская помощь, 2024)
When performing osteosynthesis for spinal instability after traumatic injury, diagnostic difficulties arise due to the migration of metal structure components to distant “atypical” anatomical areas, which is associated with the risk of neurological deficit and life-threatening conditions. This article presents a casuistic case of migration of a metal structure component through an iatrogenic opening in the occipital bone into the posterior cranial fossa in a patient who had previously undergone instrumental correction for comminuted fractures of the cervical vertebrae. It should be noted that there are no data on “spontaneous” perforation of the occipital bone by metal osteosynthesis elements in the domestic literature.